Integration of circular practices and Industry 4.0 technologies: barriers and a framework for climate change mitigation - John Wilmer Parra Llanos; Lucila Maria de Souza Campos (Gestão & Produção)
Abstract Climate change poses a significant threat to humanity, driven by factors such as global warming, natural resource depletion, and environmental pollution. This study conducts a systematic literature review to explore how the integration of circular economy practices and Industry 4.0 technologies can mitigate the impacts of climate change. Using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol, a search was conducted across the Scopus, Web of Science, EBSCO, and Science Direct databases. The results demonstrate that combining circular practices, such as reuse, reduction, and recycling, with I4.0 technologies not only reduces firms' environmental impacts but also enhances their competitiveness. However, this integration faces significant challenges, including high investment costs, a shortage of skilled labor, and organizational resistance to change. To address these challenges, the study proposes a framework to support this integration, fostering sustainable business models that optimize resource use, reduce greenhouse gas emissions, and improve business competitiveness. This work provides practical insights for researchers, policymakers, and industry professionals to address climate challenges through innovative and sustainable strategies.